WORKLOAD ANALYSIS TO DETERMINE THE OPTIMAL NUMBER OF EMPLOYEES AFTER THE HOLDING-SUBHOLDING TRANSFORMATION IN THE BUSINESS SUPPORT DIVISION OF PT PLN NUSANTARA POWER, BELAWAN GENERATION UNIT - Wilsam Pasaribu, April Yanto; Lumbanraja, Prihatin; Iskandirini, Iskandirini (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The organizational transformation through the Holding-Subholding program within PT PLN (Persero) has brought significant changes to the organizational structure and workload distribution, particularly in the Business Support Division of PT PLN Nusantara Power, Belawan Generation Unit. These changes are evident from the increased number of overtime hours due to the reassignment of several employees from the Business Support Division and the addition of new tasks. This study aims to identify the optimal number of employees by analyzing the current workload in the Business Support Division following the implementation of the Holding-Subholding program. The work time analysis was conducted using the Work Sampling method, and the employee requirements analysis was performed using the Full Time Equivalent (FTE) method, based on the guideline KEP/75/M.PAN/7/2004. The results of the study indicate that the effective working days in a year amount to 278 days, with an effective working time of 1,668 hours for a five-day workweek. Based on work sampling, the percentage of productive activities was 79.01%, non-productive activities 3.51%, and personal activities 17.47%, with a 20% allowance. The FTE workload measurement results show that in the Business Support Division, one staff position falls under the inload category, two positions under underload, and five positions under overload. The calculation also reveals a discrepancy between the actual number of employees and the ideal staffing needs, including shortages of 2 staff members in the HR Officer position, 1 in the Accounting Officer position, and 1 in the Procurement Officer position. However, there is also an excess of 1 staff member in the Finance Officer position.